Efek Induksi Gaya Mekanis Ortodonti Terhadap Perubahan Jumlah Sel Osteoblas Tulang Alveolar Gigi Tikus Pada Daerah Tarikan - Reganita Nurmaulawati Saputri; Herniyati Herniyati; Dwi Prijatmoko (Pustaka Kesehatan, 2021)
Orthodontic treatment is one treatment that can improve the dental malocclusion. Bone remodeling involves the coordination of three cell types namely osteocytes, osteoclasts, and osteoblasts. Osteoblast cells is important in the process of bone remodeling, especially in the process of bone aposition in tension side. This study aimed to analyze the changes in number of osteoblasts cell in tension side of Sprague dawley alveolar bone which induced by orthodontic force during one weeks, two weeks, and three weeks. 36 rats were divided into 6 groups, the treatment group with apllied the orthodontic force for 1 weeks (P-1), 2 weeks (P-2), and 3 weeks (P-3) and thr control group without apllied the orthodontics force group for 1 weeks (K-1), 2 weeks (K-2), and 3 weeks (K-3). Wire ligature 0,20 mm was apllied on the right region of maxillary first Molar and Incicivus, then mesially activated with maximally tension gauge of Orthodontic appliance of Ni-Ti closed coil springs. Those samples were sacrified and sliced vertically on the regio right maxillary bone with mesiodistal position, then the preparation of histological section with Hematoxilyn Eosin staining (HE) was made. The number of osteoblast cells were observed in 3 areas of tension side using microscope with 400 magnification. The result showed that the osteoblasts number of 2- and 3-weeks treatment groups were greater significantly than control group. It concluded that the induction of orthodontic appliance mechanic increased the number of osteoblast on tension area. The increasing of osteoblast number is paralel with the duration of the orthodontic appliance mechanic induction.